Climate policy versus development aid - Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2007)
Rich countries have emitted most of the greenhouse gases in the atmosphere, while poor countries will suffer most from climate change. Rich countries have therefore committed to help poor countries adapt. However, this is financed from the general development budget, and hence may do more harm than good. Furthermore, development aid also finances emission reduction. These aspects of climate policy need to be overhauled. Development assistance should consider the impact of climate change, and reduce emissions where it can, but this can be achieved by marginal adjustments to current practice.
Keywords: 330; Klimaschutz; Internationale Umweltpolitik; Entwicklungshilfe; Welt